Use of single-use negative pressure wound therapy in dehiscence of osteosynthesis of the medial and lateral malleolus: a case report - Goulart de Andrade e Souza, Danielle (Revista Feridas, 2023)
Objective: To demonstrate the use of Single-Use Negative Pressure Wound Therapy (sNPWT) at home to help promote closure by second intention of surgical dehiscence of malleolar osteosynthesis. Method: Case report obtained by physical examination of the patient, clinical evaluation of the wound and photographic record. Result: The patient presented dehiscence one month after the surgical procedure and was cleaned with antiseptic solution, laser therapy to reduce microbial load and introduced sNPWT to promote border contraction of the lesion (macrodeformation) and granulation (microdeformation) associated with the primary mesh dressing with nanocrystalline silver as a filling layer with antimicrobial action. Conclusion: Negative pressure wound therapy promoted micro and macrodeformation according to its mechanism of action, promoting a satisfactory management of the exudate, and a wound bed preparation for the final secondary closure using multilayer foam covering.